Current challenges of healthcare co-creation and testbeds - Lahtiranta Janne; Collanus Eva; Kielo-Viljamaa Emilia; Tuomisto Antti (Sosiaali- ja terveyshuollon tietojenkäsittely-yhdistys, 2025)
In the recent years, co-creation – especially in the form of testbeds – has been more and more utilized in healthcare sector. As is common in the Northern Europe, most of the testbed services are offered by public sector organizations, such as higher education institutes. These kinds of organizations have core functions, that are often defined in the law, and co-creation in one form or another, may not be included in the functions. It follows from this that the operational maturity may differ significantly from one testbed to another. This paper investigates the current state of the Finnish healthcare testbeds, their “good” and the “bad”. The data used in this review was collected during the development of Health Care Testbed Maturity Assessment instrument (HCTM). During the development, a series of so-called friendly audits were performed on Finnish testbeds, during which the testbed operators’ insider views were collected for later use alongside data used for instrument development. This article will summarize these views, provide a current view to the Finnish healthcare testbeds, and conclude with practical remarks on how to develop the maturity of Finnish healthcare testbeds.